Abd al-Rahman al-Dakhil's Stance Towards the Christian Kingdoms in Al-Andalus - Hussein Dawood, Suhair (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
This study examines the stance of Abd al-Rahman al-Dakhil towards the Christian kingdoms in Al-Andalus during his rule. Following the collapse of the Umayyad Caliphate in the Levant, Abd al-Rahman I successfully established an independent emirate in Al-Andalus, navigating both internal and external challenges. A significant aspect of his governance was his strategic response to the Christian kingdoms in northern Spain, which continuously sought to reclaim lost territories and challenge Muslim rule. The study explores his military campaigns, diplomatic efforts, and policies aimed at securing the stability of the Umayyad state. Despite initial successes in repelling Christian advances and imposing tributary agreements, internal strife within Al-Andalus weakened its ability to maintain long-term control over contested regions. The research underscores the pivotal role of political unity in sustaining territorial dominance and highlights how Abd al-Rahman al-Dakhil’s leadership shaped the early Islamic state in Iberia.